Influence of Vaginal Bacteria and d- and l-Lactic Acid Isomers on Vaginal Extracellular Matrix Metalloproteinase Inducer: Implications for Protection against Upper Genital Tract Infections - Steven S. Witkin (American Society for Microbiology, 2013)
ABSTRACT We evaluated levels of vaginal extracellular matrix metalloproteinase inducer (EMMPRIN) and matrix metalloproteinase (MMP-8) in vaginal secretions in relation to the composition of vaginal bacterial communities and d- and l-lactic acid levels. The composition of vaginal bacterial communities in 46 women was determined by pyrosequencing the V1 to V3 region of 16S rRNA genes. Lactobacilli were dominant in 71.3% of the women, followed by Gardnerella (17.4%), Streptococcus (8.7%), and Enterococcus (2.2%). Of the lactobacillus-dominated communities, 51.5% were dominated by Lactobacillus crispatus, 36.4% by Lactobacillus iners, and 6.1% each by Lactobacillus gasseri and Lactobacillus jensenii. Concentrations of l-lactic acid were slightly higher in lactobacillus-dominated vaginal samples, but most differences were not statistically significant. d-Lactic acid levels were higher in samples containing L. crispatus than in those with L. iners (P < 0.0001) or Gardnerella (P = 0.0002). The relative proportion of d-lactic acid in vaginal communities dominated by species of lactobacilli was in concordance with the proportions found in axenic cultures of the various species grown in vitro. Levels of l-lactic acid (P < 0.0001) and the ratio of l-lactic acid to d-lactic acid (P = 0.0060), but not concentrations of d-lactic acid, were also correlated with EMMPRIN concentrations. Moreover, vaginal concentrations of EMMPRIN and MMP-8 levels were highly correlated (P < 0.0001). Taken together, the data suggest the relative proportion of l- to d-lactic acid isomers in the vagina may influence the extent of local EMMPRIN production and subsequent induction of MMP-8. The expression of these proteins may help determine the ability of bacteria to transverse the cervix and initiate upper genital tract infections. IMPORTANCE A large proportion of preterm births (>50%) result from infections caused by bacteria originating in the vagina, which requires that they traverse the cervix. Factors that influence susceptibility to these infections are not well understood; however, there is evidence that matrix metalloproteinase (MMP-8) is known to alter the integrity of the cervix. In this work, we show that concentrations of vaginal extracellular matrix metalloproteinase inducer (EMMPRIN) are influenced by members of the vaginal microbial community and concentrations of d- or l-lactic acid isomers in vaginal secretions. Elevated levels of d-lactic acid and the ratio of d- to l-lactic acid influence EMMPRIN concentrations as well as MMP-8 levels. Thus, isomers of lactic acid may function as signaling molecules that alter host gene expression and influence risk of infection-related preterm birth.